Malaysian folktale classification system and digitization - Harryizman, Harun (2017)
Folktale as one of Malaysia’s intangible cultural heritage is gradually forgotten. Therefore, actions toward its preservation are necessary. Before the preservation effort can be implemented, UNESCO clearly underlined two early actions which are identification and conservation. One of the identification actions is the development of a systematic classification system and for the conservation, a storage and archive that keeps the cultural heritage in a centralized and accessible form. Both of these efforts ensure the preservation is employed systematically. However, in the context of Malaysia, both of these actions are still not implemented in the systematic preservation effort of the folktales. Based on the research gap, the research questions of this study query whether the conceptual model can be constructed to guide the classification system development, the Malaysian Folktale Classification System (MFCS) can be developed based on the integration of three important folktale units (function, motif, and type), and the Malaysian folktales can be archived digitally according to the MFCS developed. From the gap and the research questions, this study aims to systematically preserve the Malaysian folktales through the identification and the conservation efforts. As an effort to answer the research questions, the study’s objectives are to construct the conceptual model to guide the development of the MFCS, to collect and classify the literary Malaysian folktales (identification effort), to design and develop the Malaysian Folktale Digital Inventory (MFDI) prototype based on the MFCS (conservation effort), and to validate the MFDI prototype from the expert users’ judgment. The respective methods to achieve each of the research objectives are the pictorial representation, the simulation, the structural-semantic analysis, the database design, and the expert judgment. As for the findings of the study, the conceptual model is constructed and positively verified to represent the classification process visually. Guided by the conceptual model, the MFCS is successfully developed for the Malaysian folktales through the integration of the function, motif, and type units. The MFDI prototype is successfully designed and developed based on the MFCS. As for the validation of the MFDI prototype, the expert users’ perceptions and feedbacks are obtained, and they are positive at large, commenting the need of the MFDI prototype and also the MFCS for the country and the culture. Regarding the contributions of the study, the MFCS and the structural-semantic analysis method are the knowledge contributions, and the MFDI prototype is the practical contribution. The MFCS of the study is one-half of the systematic preservation effort of Malaysian folktales. The structural-semantic analysis method ensures the classification is conducted on the structure and the content of the folktales which makes the classification robust and holistic. The MFDI prototype is the other half of the systematic preservation effort, and it stores digitized folktales systematically. With the achievement of all the findings, the systematic preservation effort of the Malaysian folktale via classification and digitization is achieved.